Soft tissue profile changes after rapid maxillary expansion with a bonded expander - dos Santos, Bianca Mota; Stuani, Andrea Sasso; Stuani, Adriana Sasso; Faria, Gisele [UNESP]; Quintao, Catia Cardoso; Sasso Stuani, Maria Bernadete (Oxford University Press, 2012)
The aim of this study was to evaluate the short-and long-term treatment effects of rapid maxillary expansion (RME) on the soft tissue facial profile of subjects treated with a modified acrylic-hyrax device. The sample comprised 10 males and 10 females in the mixed dentition. Their average age was 9.3 years +/- 10 months pre-treatment (T1), with a narrow maxilla and posterior crossbite, treated with a modified fixed maxillary expander with an occlusal splint. Lateral cephalometric radiographs obtained at T1, immediately post-expansion (T2), and after retention (T3) were used to determine possible changes in the soft tissue facial profile. The means and standard deviations for linear and angular cephalometric measurements were analysed statistically using analysis of variance and Tukey's test (alpha = 0.05).The measurements at T2 differed significantly from those at T1 and T3. However, RME did not produce any statistically significant alteration (P > 0.05) in the soft tissue profile for any of the cephalometric landmarks evaluated when compared at T1 and T3. The use of a fixed expander associated with an occlusal splint did not cause significant alterations in the soft tissue facial profile at T3. This modified device is effective for preventing the adverse vertical effects of RME such as an increase anterior face height in patients with a crossbite.